Leadership efficacy in youth football: athletes and coaches’ perspective - Gomes, A. Rui (2022)
According to the Leadership Efficacy Model, leadership efficacy depends on leaders’ tendency to make linear relationships between leadership philosophy, practice, and criteria (i.e., congruence of leadership cycles). Moreover, efficacy increases if coaches make these linear relationships by using the optimal leadership profile and by considering the antecedent factors of leadership (characteristics of the leader, team members, and organizational conditions; i.e., favorability of conditions for leadership). This study compared the perceptions of athletes and their coaches regarding leadership cycles, and tested the moderator role of optimal leadership profile and leadership favorability in the relationship between leadership cycles and leadership efficacy. This study included 92 football athletes (ages less than 17 and 19 years) and respective coaches (n = 5). The evaluation protocol included measures of leadership cycles, leadership styles, leadership favorability, and sport performance perception. Athletes and coaches agreed on coaches’ need to increase their practice and criteria, but athletes also considered that coaches should better clarify their philosophy. Regression analyses confirmed that leadership congruency predicts higher perceptions of team performance in athletes. Moreover, optimal leadership profile and higher leadership favorability were associated with higher team and individual performance. However, these two factors did not moderate the relationship between leadership congruency and efficacy.